Peran Digital Marketing dalam Meningkatkan Penjualan Usaha Mikro Kecil dan Menengah (UMKM) di Kabupaten Lebak Provinsi Banten - Amelia, Maidina; Romantika, Rizki; Hasrul, Fauzan Az-zirnikh Ibnu; Pasaribu, Siti Lili Mariyanti; Sari, Arum Puspita; Sarwani, Sarwani; Sudaryana, Yayan (Jurnal PKM Manajemen Bisnis, 2025)
The rapid development of digital technology has brought significant changes to marketing strategies, especially for Micro, Small, and Medium Enterprises (MSMEs) that need to adapt to stay competitive. This community service activity aimed to enhance the understanding and application of digital marketing among MSME actors in Lebak Regency, Banten Province, as a strategy to increase their sales performance. The activity was held on June 30, 2024, at the DPRD Building of Lebak Regency, involving 25 lecturers and master's students of Management from Universitas Pamulang (Unpam) as facilitators and 50 local MSME participants. The program was carried out through a structured approach consisting of preparation, implementation, and closing stages, using a combination of material presentation and practical sessions. The results showed increased awareness and skills among MSME participants in utilizing digital platforms for marketing, such as social media, e-commerce, and content creation. This initiative implies that targeted digital marketing training can play a pivotal role in supporting MSMEs to adapt in the digital era and improve their market reach.